"Of the edgelands": broadening the scope of qualitative methodology. Issue 1 (15th June 2005) - Rapport, F; Wainwright, P; Elwyn, G
Abstract : In an editorial in a previous issue of this journal Rapport et al introduced the metaphor of the edgelands, arguing that the area between urban and rural landscapes serves to illustrate some of the difficulties of interdisciplinarity experienced by those who work in the medical humanities. In this paper the authors explore some specific issues of qualitative research methodology in health care research. The paper describes a broadening out of the scope of qualitative inquiry in social scientific research in health and social care. The paper explains why some new methodologies have emerged and how both old and new methodologies are grouped around three interlocking strands: narrative based, arts based, and redefined, methodology. In order to illustrate developments in this field, the authors present three examples of the use of these methodologies in practice: photo elicitation technique; discourse analytic, and interpretive anthropological, method. Finally the authors illustrate how these methodologies can give added value to health services research.